THE CORPORATE CONSTITUTIONALISM APPROACH IN THE FORMULATION OF CSR - Nalle, Victor Immanuel (Indonesia Law Review, 2015)
The 21st century is the era of the development of corporate social responsibility (CSR). It is encouraged by the development of the company as a business and societal entities that balances public and private interests. If there is a balance of public and private interests in the company, the application of CSR should be able to accommodate the public interest. However there are a lot of companies in Indonesia that do not involve the community in the formulation of CSR implementation model. This resulted the implementation of CSR which is often not well targeted. In that context, the theory of corporate constitutionalism becomes a relevant theory to answer this problem. The theory of corporate constitutionalism puts deliberation as one of the principles to achieve the legitimacy of decision-making in the corporation. Through a process of deliberation formulation of CSR model with the community, not just the interests of shareholders that can be accommodated but also the interests of stakeholders. Thus, CSR can actually be an instrument solvingto solve the global and local challenges.